PENGARUH KUALITAS PELAYANAN, FASILITAS DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PASIEN RAWAT INAP PADA RSUD ASEMBAGUS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Kurniawan, Amelia Tri Amanda; Arief, Mohammad Yahya; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
This research aims to determine the role of satisfaction in mediating service quality, facilities, and company image in the loyalty of inpatients at Asembagus Regional Hospital. The population in this study were all inpatients at Asembagus Regional Hospital. The sampling technique used in this research is the probability sampling method, which uses a random sampling technique. Data analysis and hypothesis testing in this research used the Partial Least Square - Structural Equation Model (PLS-SEM). The research results show that service quality has a positive and significant effect on satisfaction, facilities have a positive but not significant effect on satisfaction, company image has a positive and significant effect on satisfaction, company image has a significant effect on satisfaction, company image has a positive but not significant effect on patient loyalty, facilities has a positive and significant effect on patient loyalty, service quality has a positive and significant effect on patient loyalty, satisfaction has a positive and significant effect on patient loyalty, service quality has a positive but not significant effect on patient loyalty through satisfaction, facilities have a positive but not significant effect on patient loyalty through satisfaction, company image have a positive and significant effect on patient loyalty through satisfaction.